Chapter Kr in the Gospels - Parpulov, Georgi (Arbeiten zur neutestamentlichen Textforschung, 2019)
Thirty-three internationally renowned scholars of the text and transmission of the New Testament offer original contributions on ancient manuscripts and digital editing in honour of Klaus Wachtel, a pioneer in the use of computers to edit the New Testament. The individual chapters in English, German and French represent new research on a wide range of important manuscripts, early translations and editorial approaches.